2013
DOI: 10.1080/09603123.2013.835032
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of cadmium-induced toxicity: a review

Abstract: Cadmium is a widespread toxic pollutant of occupational and environmental concern because of its diverse toxic effects: extremely protracted biological half-life (approximately 20-30 years in humans), low rate of excretion from the body and storage predominantly in soft tissues (primarily, liver and kidneys). It is an extremely toxic element of continuing concern because environmental levels have risen steadily due to continued worldwide anthropogenic mobilization. Cadmium is absorbed in significant quantities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
287
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 588 publications
(340 citation statements)
references
References 145 publications
12
287
0
6
Order By: Relevance
“…BIS (2012) proposed that the maximum desirable limit of cadmium is 3 lg/L without any relaxation in the absence of another source. Surface waters have been contaminated by industrial wastes, plating works, plants manufacturing cadmium pigments, textile operations, cadmium-stabilized plastics, or nickel-cadmium batteries, or by effluents from sewage treatment plants (Rani et al 2014). …”
Section: Cadmiummentioning
confidence: 99%
“…BIS (2012) proposed that the maximum desirable limit of cadmium is 3 lg/L without any relaxation in the absence of another source. Surface waters have been contaminated by industrial wastes, plating works, plants manufacturing cadmium pigments, textile operations, cadmium-stabilized plastics, or nickel-cadmium batteries, or by effluents from sewage treatment plants (Rani et al 2014). …”
Section: Cadmiummentioning
confidence: 99%
“…Based on epidemiological data, the IARC states that there is no evidence of unequivocal carcinogenic effects of Cd [278][279][280][281][282] . However, many animal studies have demonstrated the ability of Cd to determine various tumors, including HCC.…”
Section: Cadmiummentioning
confidence: 99%
“…Release of Cd into the environment resulting from its use poses a potential danger to the general population and represents major health hazards. Exposure to Cd has harmful effects on the cells and tissues in a variety of organs, including the liver and kidney (4). Acute and chronic contacts with Cd lead to collection of the metal in the liver, inducing hepatotoxicity (5,6).…”
Section: Introductionmentioning
confidence: 99%